2020
DOI: 10.3928/23258160-20201104-04
|View full text |Cite
|
Sign up to set email alerts
|

OCT Assistance in Identifying Retinal Breaks in Symptomatic Posterior Vitreous Detachments

Abstract: BACKGROUND AND OBJECTIVE: Posterior vitreous detachment (PVD) is a separation of the posterior hyaloid from the retina that manifests as photopsias and floaters. Optical coherence tomography (OCT) has demonstrated posterior vitreous opacities (PVOs) that may correlate with Shaffer's sign, which may correlate with retinal breaks. PATIENTS AND METHODS: Patients with symptomatic PVDs were retrospectively reviewed at a single institution by a single provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
0
6
1
Order By: Relevance
“…In a study of donor eyes, Wang et al reported an increase in age-related migration of the posterior border of the vitreous base in men compared with women. 15 In addition, previous studies 11,16,17 have reported trends of retinal tears in younger patients; however, our study found there was a significant association between the two.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…In a study of donor eyes, Wang et al reported an increase in age-related migration of the posterior border of the vitreous base in men compared with women. 15 In addition, previous studies 11,16,17 have reported trends of retinal tears in younger patients; however, our study found there was a significant association between the two.…”
Section: Discussioncontrasting
confidence: 77%
“…However, only few studies have evaluated OCT imaging correlates of retinal tear in acute PVD. 11,16,23 The most recent study by Ansari et al evaluated 78 patients and found the presence of PVOs has a sensitivity and specificity of 76% and 75.5%, respectively, in detecting retinal tears in patients with symptomatic PVD. Negative predictive value and PPV were 87% and 59.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard of care is to carefully observe the entire retina with ophthalmoscopy and scleral depression for the presence of breaks. However, clinical diagnosis is not perfect and OCT may be superior for identification of peripheral pathology ( 32 , 33 ). In this paper, we have presented several examples of tractional, rhegmatogenous, and exudative detachments and highlighted ways in which WF-OCT may be utilized in the diagnosis and monitoring of these diseases in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the absence of clinical vitreous hemorrhage and VHRDs indicated a 94% chance that no retinal breaks were present. 4 Thus, a “negative” or normal SD-OCT imaging in setting of an acute PVD seems to have a strong negative predictive value for a peripheral rhegmatogenous event, especially if paired with conventional ophthalmoscopy with scleral depression.…”
Section: Vitreous Hyperreflective Dots As Biomarker Of a Rhegmatogeno...mentioning
confidence: 97%